Liberdade sexual e o mundo do desejo: um estudo de O amante de Lady Chatterley na literatura e no cinema - Souza, José Bezerra de (2024)
Considering the idea that every translation merely illustrates an aesthetic discussion limits its true role, as more than debating about form, today, content is also important, especially when it resonates socially, politically, and culturally. From this perspective, we will discuss audiovisual adaptations of Lady Chatterley’s Lover (1928), a novel by D. H. Lawrence, focusing on the theme of sexual freedom of the protagonist characters. The study will depart from this “naked freedom” and/or its absence due to the external and internal conventions experienced by the characters, as well as the period of production and reception. Furthermore, as it is a classic of English literature, having had numerous adaptations for both cinema and television, we will seek to critically examine to what extent the selected media, namely: L’amant de lady Chatterley (1955), Lady Chatterley’s Lover (1981), and Lady Chatterley (2006), reinforce Lawrence’s question of sexual freedom, contributing to the construction of the body-guy genre, that is, how the emergence of a Lawrencian cinematic style became a model for the future of this genre. To conduct the research, we will consider some concepts and perspectives on translation as presented by Cattrysse (1992), Arrojo (1997), Jakobson (1991), and Lefevere (2007), in addition to adaptation principles with Hutcheon (2013) and Stam (2006), the idea of sex, pornography, and obscenity in cinema by Gerace (2015) and Freixas and Bassa (2000), and studies on Lawrence’s work, including Casey (2003), Lehman & Hunt (2010), and Silva (2017), among others. Following our descriptive-interpretative research, we conclude that each director adopted distinct approaches to represent changes in social attitudes towards sex and sexual freedom over time, and the intersection between literature and cinema, through translation as rewriting, allowed us to have a broad view of the changes faced by the book and its adaptations. Thus, the study of D. H. Lawrence’s rewrites allows for parallels to be drawn between different representations of sexuality, despite censorship challenges. Finally, we observe that Lady Chatterley’s Lover did not directly impact the body-guy genre; rather, it was also influenced by technological advancements and cultural changes. However, Lawrence’s work continues to serve as a foundation for exploring sexuality and human relationships in cinema, thus enriching the experience of studying cinematic rewrites and celebrating the human capacity to reinvent, revitalize, and reinforce timeless stories.